2022
DOI: 10.7759/cureus.30941
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality After Rib Fracture in Elderly Patients (>65 Years Old) Compared to a Younger Cohort (≤65 Years of Age) at Doctor Hospital Renaissance Health

Abstract: Background: Traumatic rib fracture is a major cause of morbidity and mortality. Recent studies highlight the inadequacy of age and the number of rib fractures (NRFs) to assess patients' care needs, which may unnecessarily increase the burden of intensive care unit (ICU) admissions. Therefore, we sought to clarify the clinical outcomes of patients admitted to a level I trauma center with multiple blunt-trauma rib fractures by age and fracture location.Methods: We performed a retrospective cohort study of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Older patients often have decreased bone density due to conditions like osteoporosis, making their ribs more susceptible to fractures even with minor trauma. 10 Complications of rib fractures include pneumothorax, hemothorax, pulmonary contusion, and rib displacement leading to lung injury, managed through pain control, respiratory support if necessary, chest physiotherapy, rib fracture stabilization with splinting or bracing, and monitoring for and treating complications such as pneumothorax or hemothorax. writing -review and editing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older patients often have decreased bone density due to conditions like osteoporosis, making their ribs more susceptible to fractures even with minor trauma. 10 Complications of rib fractures include pneumothorax, hemothorax, pulmonary contusion, and rib displacement leading to lung injury, managed through pain control, respiratory support if necessary, chest physiotherapy, rib fracture stabilization with splinting or bracing, and monitoring for and treating complications such as pneumothorax or hemothorax. writing -review and editing.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that an increased number of fractured ribs is associated with higher mortality rates, particularly in older individuals. Older patients often have decreased bone density due to conditions like osteoporosis, making their ribs more susceptible to fractures even with minor trauma 10 …”
Section: Discussionmentioning
confidence: 99%
“…These complications impose the substantial financial burden on healthcare systems and have particularly detrimental effect on the elderly, who have a higher risk of developing complications. 4,5 Rib fractures are not limited to skeletal injuries within the clinical environment; they can also cause substantial harm to soft tissues, especially when they are accompanied by traumatic chest wounds. These injuries manifest as sudden discomfort that is worsened by respiratory actions and have the potential to greatly hinder pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent evidence has questioned this paradigm, especially in the pan-scan era. [23][24][25][26][27][28] In the development of the RIBS, age was offered to the model as a candidate predictor at every step given its historical significance, and was consistently cut from the model due to providing no significant predictive power. This validation study will reexamine the issue of age and its impact on predicting complications once again.…”
mentioning
confidence: 99%
“…There is an abundance of historical evidence for the role of age 2,3,14–22 in predicting morbidity, mortality, pneumonia and prolonged length of stay. However, more recent evidence has questioned this paradigm, especially in the pan-scan era 23–28 . In the development of the RIBS, age was offered to the model as a candidate predictor at every step given its historical significance, and was consistently cut from the model due to providing no significant predictive power.…”
mentioning
confidence: 99%